An Attenuated Escherichia coli K88ac LT(S63K)ΔSTb Efficiently Provides Protection Against Enterotoxigenic Escherichia coli in the Mouse Model - Zhang, Xinyu; Yu, Shupei; Cheng, Darong; Feng, Yu; Yang, Yuefei; Sun, Huaichang; Ding, Jiabo; Wang, Fang (Frontiers in Veterinary Science, 2021)
To develop an attenuated vaccine candidate against K88ac enterotoxigenic Escherichia coli (ETEC), a novel Escherichia coli (E. coli) K88ac LT(S63K)ΔSTb with LT(S63K) mutation and ST1 deletion was generated using site mutagenesis and λ-Red homologous recombination based on wild paternal ETEC strain C83902. E. coli K88ac LT(S63K)ΔSTb showed very similar fimbriae expression and growth kinetics to the wild strain C83902, but it was significantly attenuated according to the results of a rabbit ligated ileal loop assay and mouse infection study. Oral inoculation with E. coli K88ac LT(S63K)ΔSTb stimulated the mucosa immune response and induced the secretion of IgA to K88ac in the intestines in mice. A challenge experiment revealed that the attenuated strain provided efficient protection against C83902 in the following 7 days and at the 24th day post-inoculation, suggesting that the attenuated isolate could act as an ecological protectant and vaccine in preventing K88ac ETEC.